The Phonological Interference of Acehnese in Pronouncing Indonesian Language - Suhery, Dedy; Idami, Zahratul; Wati, Shafrida (Universitas Pendidikan Mandalika, 2024)
Linguistic issues such as interference and integration frequently arise in multilingual environment, which frequently result in barriers to second language production. This study examines at how language interaction between Acehnese and Indonesian has affected the Indonesian language in Langsa, with a particular emphasis on consonant variations and interference. The objective of this study was to investigate the influence of phonological interference on Acehnese speakers when speaking the Indonesian language, with a specific focus on observing variations in consonant sounds using auditory means. The study conducted a detailed examination of common variances in Indonesian pronunciation among Acehnese speakers. This qualitative research was carried out in Langsa, Aceh Province, involving 40 individuals who are native speakers of Acehnese. The participants consisted of 20 males and 20 females, encompassing a range of ages. The collected data was evaluated using the PRAAT software. The findings revealed that there was interference in pronunciation, particularly in the form of devoicing, which is the absence of vowel resonance. This was observed in the words